AbMTI: adventure based mental toughness inventory for post COVID-19 pandemic era / Mohd Shariman Shafie ... [et al.] - Shafie, Mohd Shariman; Md Taff, Md Amin; Mohd Sidi, M.Adli; Mohamed Afandi, Mohamed Azizul; Mohd Said, Omar Firdaus; Johannis, Nik Jazwiri (2021)
The COVID-19 pandemic has increased concerns about public well-being and mental toughness. Accordingly, the concept of mental toughness is highly relevant to the COVID-19 pandemic and there has been a rapid growth in research assessing the consequences of the coronavirus on individual mental toughness. In line with the issue, adventure-based training program believed to becomes part and parcel for any organization or institution in post pandemic era as part of the solutions in purpose to regain or improve individual mental toughness. However, there is limited measurement tool to assess mental toughness in adventure-based program. Now, it is a call to invent solutions. The innovation of Adventure- based Mental Toughness Inventory (AbMTI) rooted in the modified Design and Development Research (DDR: Saedah et. al., 2020). A total of 14 field's experts and 507 respondents was involved in a series of analysis using Structural Equation Modelling (SEM). The AbMTI potentially benefited to Malaysian active adventure-based training practitioners and professional. The AbMTI also becomes a part of the solutions to regain or improve mental toughness to more than 50% of Malaysian population that involved with active recreation (IYRES: Malaysia Sports Index, 2019). AbMTI offers new perspective of mental toughness and shifted to be more relevant towards challenges and opportunities in adventure- based training program setting. To conclude, AbMTI prepares and helping the adventure- based training industry to come back stronger after COVID-19.